Efeitos das impurezas iônicas em líquidos isotrópicos e em cristais líquidos nemáticos - Almeida, Roberta Rarumy Ribeiro de (2012)
The presence of ions in samples of nematic liquid crystals (NLC) is responsible for significant effects on the molecular orientation of the system. For practical applications, as well as for fundamental purposes, it is important to investigate the influence of these ions on the electrical response of the sample. The ionic adsorption phenomenon generates a surface electric field that, in turn, can affect the molecular orientation of the sample, producing instability in the orientation of the director and modifying the electrical response of the system. To establish the equilibrium distribution of charges on the nematic medium, the classical Maxwell-Boltzmann (MB) distribution is generally considered. Recently, however, a different statistical distribution was used to describe ionic liquids with particular emphasis on the behavior of the double layer capacitance. Here, the Poisson-Fermi theory is invoked to investigate the effects of adsorption phenomena and external fields in electrolytic cells of finite thickness. In the absence of adsorption, the expressions for the electrical potential across the sample and for the differential capacitance of the double layer are established as a function of the applied voltage. In the presence of adsorption, without external fields, the main equations of the model are presented and analytically solved in the limit of small potential. In this context, the (chemical and electrical) potentials, as well as the differential capacitance of the double layer, are determined and investigated as a function of the density of ions in the bulk and the adsorption energy. The profile of capacitance is also explored in terms of the difference of potential connected to the adsorption process. Moreover, the fundamental equations of the Poisson-Boltzmann theory are recalled to report the effects of the selective adsorption of ions on the anchoring energy of NLC. Following this line of research, in the context of Fermi-Dirac (FD) statistical, we establish analytical expressions for the dielectric and flexoelectric anchoring energy of the system. In addition, we determined the anchoring energy of ionic origin for the general case in which external fields is applied without taking into account the effects of adsorption.